The Use of Infographic to Enhance EFL Students’ Reading Interest - I Gede Krisna Meialldy (Journal of Educational Study, 2021)
This study was designed to review previous studies conducted by the other researchers related to the utilization of infographics to enhance the EFL students’ reading interest and design a scenario of utilizing the infographics in the classroom to enhance the students’ reading interest. The paper conducted library research to collect the data. Several studies that fulfilled the criteria were reviewed in the data collection. It was found that many other researchers found positive impacts from the utilization of infographics. It was also found that the utilization of infographics to enhance the students’ reading interest was not very difficult since the high development of technology nowadays can help teachers to design the infographic using software and online platforms easier. The last result found were the benefits acquired from the utilization of infographics, namely reducing the students’ boredom, increasing their will to read, and developing their ability to think critically and organize ideas.